Knowledge in the development of economies : institutional choices under globalisation - Sacchetti, Silvia (Edward Elgar Publishing Ltd. CheltenhamGB, 2009)
Aims at providing a specific perspective on the role of knowledge for the analysis of economic development issues. Emphasises knowledge, creativity and critical thinking as forces in processes of change, including those transforming the rules governing economic systems.